2006
DOI: 10.1108/09590550610673590
|View full text |Cite
|
Sign up to set email alerts
|

Online shopping portals: an option for traditional retailers?

Abstract: Purpose -The purpose of the paper is to examine the benefits delivered to traditional retailers from using shopping portals as their entry mechanism to the online trading environment. The paper also aims to highlight the possible drawbacks inherent in such an approach. Design/methodology/approach -A case study approach was used with an online portal, combining documentary analysis and semi-structured interviews, using a team-based interviewing approach. This facilitated the development of a multi-layered pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
0
23
0
3
Order By: Relevance
“…The discussed material and findings from the previous research have shown that most authors have studied the phenomenon of the online shopping from the perspective of marketing (Parsons, 2002;Rowley, 2000;Monsuwe et al, 2004;Al-Debei et al 2015). Some of them discussed this phenomenon with a purpose to find general features that may lead to the improvement of the information technologies used for shop development (Yu et al, 2007;Kaufman et al, 2005). The economic aspects of the shopping experience have been studied more rarely by comparing to the mentioned ones, and the economic motives that may explain the shopping behaviours have not been studied with a purpose to classify them at all.…”
Section: Factors Determining Motives That Stimulate the Intensity Of mentioning
confidence: 99%
“…The discussed material and findings from the previous research have shown that most authors have studied the phenomenon of the online shopping from the perspective of marketing (Parsons, 2002;Rowley, 2000;Monsuwe et al, 2004;Al-Debei et al 2015). Some of them discussed this phenomenon with a purpose to find general features that may lead to the improvement of the information technologies used for shop development (Yu et al, 2007;Kaufman et al, 2005). The economic aspects of the shopping experience have been studied more rarely by comparing to the mentioned ones, and the economic motives that may explain the shopping behaviours have not been studied with a purpose to classify them at all.…”
Section: Factors Determining Motives That Stimulate the Intensity Of mentioning
confidence: 99%
“…Ahead of television or catalogue shopping, Internet shopping, otherwise known as e-tailing or eshopping, represents the most rapidly emerging form of non-store retailing today (Kennedy and Coughlan, 2006). Current advancements and innovations within the field of non-store retailing have drastically escalated the pressures of competition endured by many traditional, store retailers (Kennedy and Coughlan, 2006). Pure e-tailers (e.g.…”
Section: E-tailing -Adoption Requirements and Attitudesmentioning
confidence: 99%
“…Toliau nurodomi svarbiausi jų: (7) verslo modelis, apimantis procesus interneto svetainėje ir parduotuvėje (angl. bricks and clicks business model) (parduotuvių tinklas leidžia vartotojui užsakyti prekes internete, tačiau savo užsakymą jis atsiima vietinėje parduotuvėje) (Kennedy et al, 2006); (8) elektroninės parduotuvės verslo modelis (angl. e-shop business model) (elektroninė parduotuvė -tai išplėstas prekių ir paslaugų pateikimas internete.…”
Section: Verslo Modelių įVairovė Prekybos įMonėseunclassified
“…direct sales model) (kai prekės rodomos ir parduodamos prekių vartotojams bei tiesiogiai asmeniškai pristatomos) (Smith, 2006); (14) prekybos televizijoje verslo modelis (angl. TV shopping business model) (pardavėjas rodo prekes per televiziją, sudaro sandorį su pirkėju nacionalinėje rinkoje, o jį sudarius, pristato prekes nurodytu adresu) (Kennedy et al, 2006). Remiantis US Census Bureau (2009) duomenimis, atskleista, kad 2,2 % visų JAV mažmeninės prekybos įmonių pardavimų sudaro pardavimai, kai taikomi šioje kategorijoje įvardinti verslo modeliai.…”
Section: Verslo Modelių įVairovė Prekybos įMonėseunclassified